Aggregation, solubility and cadmium-adsorption capacity of CuO nanoparticles in aquatic environments: Effects of pH, natural organic matter and component addition sequence. (15th May 2022) - Xiao, Yinlong; Tang, Wei; Peijnenburg, Willie J.G.M.; Zhang, Xiaohong; Wu, Jun; Xu, Min; Xiao, Hong; He, Yan; Luo, Ling; Yang, Gang; Chen, Chao; Tu, Lihua
Abstract: Nanoparticles (NPs), heavy metals and natural organic matter may co-exist in the water bodies. Currently, knowledge on their interaction effects on the behaviors and fates of NPs and heavy metal ions is rather limited, which is critical to comprehensively understand their environmental risk. In this study, the aggregation, solubility and Cd-adsorption of CuO NPs co-existing with humic acid (HA) and Cd 2+ upon different solution pH and contact sequences were determined. In the ternary systems of CuO NPs, HA and Cd 2+, pH was more important than the contact sequence of the components in affecting the NP aggregation, while the contact sequence was a predominant factor in determining the NP solubility. Pre-equilibration of CuO NPs and HA before addition of Cd 2+ resulted in the highest solubility and lowest aggregation of the NPs, relative to other sequences of addition of the components. The adsorption capacity of CuO NPs for Cd-ions increased with an increasing pH value from 5 to 9. HA significantly enhanced the Cd-adsorption capacity of CuO NPs at pH 7 and 9, while at pH 5 a non-significant effect was observed. The results are helpful to better estimate the behaviors and fates of CuO NPs and Cd 2+ when they coexisting in natural waters. Highlights: The sequence of addition of Cd 2+ /HA/CuO NPs dominantly affected the NP solubility. The joint effects of Cd 2+ and HA on CuO NP aggregation were mainly affected by pH. Cd adsorption on CuO NPs was positively correlated with solution pH. HA enhanced Cd adsorption on CuO NPs at pH 7 and 9, yet no effect at pH 5. Addition sequence effect on the CuO NP behavior was validated in a natural water.